Preservation of cardiac functions post myocardial infarction in vivo by a phenylboric acid-grafted hyaluronic hydrogel with anti-oxidation and accelerated degradation under oxidative microenvironment. (1st June 2022) - Wang, Shuqin; Yao, Yuejun; Zhou, Tong; Xie, Jieqi; Ding, Jie; Cao, Wangbei; Shen, Liyin; Zhu, Yang; Gao, Changyou
Abstract: Excessive oxidative stress and inflammatory responses can exacerbate the pathological conditions of left ventricular (LV) myocardium and even lead to heart failure post myocardial infarction (MI). Intramyocardial injectable antioxidative hydrogels without loading of any cells, genes or cell growth factors are attractive for the translation in clinical therapy. In this study, a self-adaptive, degradable and antioxidative hydrogel (R gel) was prepared by a Schiff base reaction between adipic acid dihydrazide (ADH)-modified and phenylboric acid (PBA)-grafted hyaluronic acid (HA-ADH-PBA) and oxidized dextran (Ox-Dex) with aldehyde groups. Compared to the non-reactive control hydrogel (N-R gel), the R gel exhibited high efficiency in scavenging excessive ROS in vitro and in vivo, and protected cells from oxidative damage in infarcted rat myocardium in vivo, as demonstrated by significantly reduced cell membrane peroxidation and apoptosis, suppressed inflammation, preserved cardiac functions, and promoted LV vascularization. The expressions of key genes associated with the inflammation in short term (3 d) and cardiomyocyte functions in long term (8 w) were investigated to explore the mechanisms in a molecular level.